Hierarchical Design Method for Micro Device - Zheng Liu; Hua Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Traditional mask-beginning design flow of micro device is unintuitive and fussy for designers. A hierarchical design method and involved key technologies for features mapping procedure are presented. With the feature-based design framework, the model of micro device is organized by various features in different designing stages, which can be converted into each other based on the mapping rules. The feature technology is the foundation of the three-level design flow that provides a more efficient design way. In system level, functional features provide the top level of schematic and functional description. After the functional mapping procedure, on the other hand, parametric design features construct the 3D model of micro device in device level, which is based on Hybird Model representation. By means of constraint features, the corresponding revision rules are applied to the rough model to optimize the original structure. As a result, the model reconstruction algorithm makes benefit for the model revision and constraint features mapping process. Moreover, the formulating description of manufacturing features derivation provides the automatic way for model conversion. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2490